2021
DOI: 10.4014/jmb.2012.12016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Allyl Isothiocyanate on the Soil Microbial Community Structure and Composition during Pepper Cultivation

Abstract: Allyl isothiocyanate (AITC), as a fumigant, plays an important role in soil control of nematodes, soilborne pathogens, and weeds, but its effects on soil microorganisms are unclear. In this study, the effects of AITC on microbial diversity and community composition of Capsicum annuum L. soil were investigated through Illumina high-throughput sequencing. The results showed that microbial diversity and community structure were significantly influenced by AITC. AITC reduced the diversity of soil bacteria, stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In Gao's study, A‐ITC reduced the diversity of soil bacteria, stimulated the diversity of the soil fungal community, and significantly changed the structure of fungal community. A‐ITC decreased the relative abundance of dominant bacteria Planctomycetes , Acinetobacter , Pseudodeganella , and RB41, but increased that of Lysobacter , Sphingomonas , Pseudomonas , Luteimonas , Pseudoxanthomonas , and Bacillus at the genera level, while for fungi, Trichoderma , Neurospora , and Lasiodiplodia decreased significantly and Aspergillus , Cladosporium , Fusarium , Penicillium , and Saccharomyces were higher than the control 35 …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In Gao's study, A‐ITC reduced the diversity of soil bacteria, stimulated the diversity of the soil fungal community, and significantly changed the structure of fungal community. A‐ITC decreased the relative abundance of dominant bacteria Planctomycetes , Acinetobacter , Pseudodeganella , and RB41, but increased that of Lysobacter , Sphingomonas , Pseudomonas , Luteimonas , Pseudoxanthomonas , and Bacillus at the genera level, while for fungi, Trichoderma , Neurospora , and Lasiodiplodia decreased significantly and Aspergillus , Cladosporium , Fusarium , Penicillium , and Saccharomyces were higher than the control 35 …”
Section: Discussionmentioning
confidence: 85%
“…A-ITC decreased the relative abundance of dominant bacteria Planctomycetes, Acinetobacter, Pseudodeganella, and RB41, but increased that of Lysobacter, Sphingomonas, Pseudomonas, Luteimonas, Pseudoxanthomonas, and Bacillus at the genera level, while for fungi, Trichoderma, Neurospora, and Lasiodiplodia decreased significantly and Aspergillus, Cladosporium, Fusarium, Penicillium, and Saccharomyces were higher than the control. 35 In addition, isothiocyanate hydrolase promoted fungal growth in the presence of ITCs, and it contributed to the virulence of S. sclerotiorum on glucosinolate-producing plants. 3 In Pectobacteria and Pseudomonas syringae, SaxA was the enzyme responsible for the breakdown of 2PE-ITC, and therefore contributing to their virulence on Brassica plants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported soil bacterial community dynamics in relation to the death rate of P. notoginseng in a continuous cropping system [36]. AITC decreased the relative abundances of dominant bacteria, Planctomycetes, Acinetobacter, Pseudodeganella, and RB41, but increased those of Lysobacter, Sphingomonas, Pseudomonas, Luteimonas, Pseudoxanthomonas, and Bacillus, at the genus level in pepper [37]. However, in tomato, there were signi cant increases in the relative abundances of probiotics, such as Sphingomonas and Streptomyces, following AITC fumigation [31].…”
Section: Discussionmentioning
confidence: 99%
“…In pepper soil, AITC soil fumigation decreased the richness of Planctomycetes , Acinetobacter , Pseudodeganella , and RB41, but increased those of Lysobacter , Sphingomonas , Pseudomonas , Luteimonas , Pseudoxanthomonas , and Bacillus , at the genus level [ 48 ]. In tomato soil, there were significant increases in the richness of probiotics, such as Sphingomonas and Streptomyces , following AITC fumigation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%